Isolation and adaptation of Pseudomonas pseudoalcaligenes from a cyanidation process effluent of auriferous minerals - Arias-Arce, Vladimir Alejandro (2023)
This work describes the isolation and selection of bacterial strains of the genus Pseudomonas in Cetrimide, Acetamide and King B Agar media, from effluents of the leaching process and from the tailings deposit of the gold ore processing plant, Caraveli - Arequipa. Subsequently, the adaptation was made in Modified Mineral Medium (M9M), to different concentrations of sodium cyanide, to evaluate the tolerance and degradation of the CN- radical. The results of sowing in different nutrient media allowed us to observe changes in coloration with a change from clear to intense red in Acetamide Medium and from clear to fluorescent green in King B Agar Medium, revealing the presence of P. pseudoalcaligenes bacteria. Similarly, during the adaptation process of a strain whose initial cell population was 2.0E+06 CFU/mL, in media supplemented with 50, 100, 150, 200 and 250 ppm of Free Cyanide, at the following conditions: temperature of 30°C, pH of 10. 5, stirring at 150 rpm and in a period of 72 hours; it was observed that the strains present in the media of 50 and 100 ppm of Free Cyanide present resistance and show growth, and on the contrary, the strains in higher concentration of cyanide show limited growth and adaptation action.